Main features and isolation technique mesenchymal stem cells from wharton’s jelly - Vo, Thi Hanh Thao; Nguyen, Phuong Thao Tien; Nguyen, Van Mao; Tran, Nam Dong; Nguyen, Thi Hieu Dung; Sara, Cruciani; Margherita, Maioli (Tạp chí Y Dược Huế, 2024)
Background: Wharton’s jelly-derived mesenchymal stem cells are highly homogeneous cells population, easily expanded, especially they can bring potential applications. However, their yield depends on the method of cells extraction conducted. Our research includes two purposes: 1/Procedure for isolating and differentiating mesenchymal stem cells from Wharton’s jelly, 2/Determining the main features of mesenchymal stem cells isolated from Wharton’s jelly. Materials and methods: Umbilical cords (UCs) were harvested from the department of Pediatrics at Sassari Hospital, Italy, from healthy full-term pregnant women who did not undergo cesarean section. After isolating Wharton’s jelly from UCs, the samples were cultured in a medium containing DMEM 78%, Serum 18%, L-glutamine 2%, Pen/strept 2%. The fibroblast-like cells obtaining after isolation were identified by markers on the surface which are special markers of mesenchymal stem cells. Besides, they were cultured to differentiate into osteocytes, chondrocytes and adipocytes. After differentiation, we used special chemicals to recognize each of line. Results: After 2 weeks, fibroblast-like cells started to attach to bottom of the flasks. They can differenciate into osteocytes, chondrocytes and adipocytes. The majority of isolated Wharton’s jelly-mesenchymal stem cells (WJ-MSCs) population showed positivity for CD34 and CD117 surface markers, while a little percentage of cells showed positivity for CD45 marker. The 95.8% of all stem cells analyzed (CD34+/CD117+) were alive. Conclusions: Fibroblast-like cells isolating from Wharton’s jelly which can differenciate into adipocytes, osteocytes, chondrocytes and show positivity for CD34, CD117 are mesenchymal stem cells